Volleyball passing model through game-based approach - Karisman, Vicki Ahmad; Supriadi, Dedi (Journal Sport Area, 2022)
Passing in volleyball is highly significant to support the game. Good passing will determine the course of attack and defense in the game. This research aims at creating volleyball passing models to improve students’ passing skills. It uses the method of ADDIE (Analyze, Design, Develop, Implement, and Evaluate). The analysis stage is to identify the source of the cause of the performance gap. The design stage is, verifying the desired performance, and the appropriate test method. The develop stage, namely, conducting, and validating learning resources. The implementation stage is preparing a learning environment and involving participants. The evaluate stage, namely, assessing the quality of learning processes, and products, both before and after implementation. Participants in this study are elementary school students who are in the fifth grade, as many as 64 people. The instrument used in this study is a test of passing up and passing down volleyball. This research found: (1). Based on the analysis carried out, passing is a crucial skill in volleyball games, however, students still experience various obstacles in their learning and motor skills. (2). The design stage is to inventory the tasks that students will do related to volleyball learning. (3). The develop stage has produced 13 games of volleyball passing model content which were validated by experts, and the proper media was chosen to help learning volleyball passing. (4). At this stage, the passing model is applied to the participants. (5). The evaluation results show significant results from the volleyball passing model through a game-based approach to volleyball passing skills. Therefore, it can be concluded that the volleyball passing model through game-based approach can be used in volleyball learning to improve the underhand and overhand passing skills.